Evaluation of a vegetable meat made with Pigeon Pea (Cajanus cajan (L.) Huth), Lentils (Lens culinaris Medik) and Chia (Salvia hispanica L.) - Castro García, Alex; Jácome Reyes, Sarly (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
The nutritional values of pigeon pea, lentils and chia are factors to consider promoting nutrition and providing healthy alternatives, seeking to improve people’s quality of life. The objective of this research was to evaluate the nutritional contribution, physicochemical, sensory and microbiological parameters of a vegetable meat made from pigeon pea and lentils, fortified with chia and vacuum-packed. Quantitative variables (pH, humidity, proteins, carbohydrates, fats, ashes and fiber), qualitative (color, smell, taste and texture) and microbiologicals (total coliforms, molds and yeasts) were evaluated. The treatments were T1 (55 % lentil, 40 % pigeon pea and 5 % chia), T2 (50 % lentil, 45 % pigeon pea and 5 % chia) T3 (40 % lentil, 55 % pigeon pea and 5 % chia) and T4 (control, 50 % lentil and 50 % pigeon pea). 30 experts were considered for sensory acceptance in terms of color, smell, taste and texture. The vegetable meat from pigeon pea, lentil and chia vacuum-packed, had a great nutritional contribution. T3 had the best values of proteins, carbohydrates, fats, ashes, fiber and acceptable values of pH and humidity, being the best treatment. The lentil used in the highest percentage (T3), obtained greater sensory acceptance, presenting better characteristics in terms of color, smell, flavor and texture, demonstrating positive organoleptic properties in the final product. The microbiological analysis performed showed values that are within the provisions of the respective standard.